QUATERNARY BASALTS FROM ROMANIA - CHARACTERISTICS AND NON-CONVENTIONAL USES - Marica, S. (Bulletin of the Geological Society of Greece, 2004)
This paper presents an advanced stage of research work regarding the exploitation of natural volcanic rocks (basalt, andésites, tuffs) that are not to be polished but that can be cut into thin tiles and be cover with different inorganic and organic films. The basalt, andésite and tuff samples from some quarries proved to have very good cutting parameters, linear thermal expansions with a temperature between 5.67 and 8.85 x106C"1 for basalts and andésites and between 0.05 and 3.82 x106 C"1 for tuffs. The classic ceramic coating process used glaze with grinding fineness. The resulting surfaces are glossy, uniformly covered from a decorative aspect and by a variety of colour, suitable for various external and internal applications. The non-conventional coating by oxy-gas flame thermal spraying process on basalt frits with a grinding fineness between 100 and 70 μπι, resulted in rough, dark coloured surfaces, suitable for floors with high compressive strengths.